Imperfect Markets versus Imperfect Regulation in US Electricity Generation - Cicala, Steve (American Economic Review, 2022)
This paper evaluates changes in electricity generation costs caused by the introduction of market mechanisms to determine production in the United States. I use the staggered transition to markets from 1999 to 2012 to estimate the causal impact of liberalization using a differences-in-difference design on a comprehensive hourly panel of electricity demand, generators’ costs, capacities, and output. I find that markets reduce production costs by 5 percent by reallocating production: gains from trade across service areas increase by 55 percent based on a 25 percent increase in traded electricity, and costs from using uneconomical units fall 16 percent. (JEL L51, L94, L98, Q41, Q48)